ISTBAT OF MARRIAGE IMPLEMENTATION FOR MARRIAGE AFTER ENACTMENT OF LAW NO. 1 OF 1974 - Baidhowi, Baidhowi; Latifiani, Dian (Journal of Islamic Law Studies, 2021)
Itsbat of marriage reserved for marriage have not been recorded and the case before Law No. 1 of 1974 (Marriage Law). The problem arises when many marriages that have been performed and are not listed that under the Act including marriage under hand, confirmed that happened after Marriage Law, then how is marriage legitimacy? Statement of problems is how is Judge Consideration in the Religious Court Judgment No. 0011/Pdt.P/2016/PA.Mkd granted that itsbat marriage happened after enactment of Law No. 1 of 1974? This study uses normative legal research, critical and ana- lytical and many library research. The data collection method data carried out in the documentation and analyzed qualitatively. Discussion is composed of two sub, the decision analysis, and offer legal alternatives. Conclusion of Religious Court (Pengadilan Agama/PA) Mungkid which granted itsbat of marriage to the marriage after Marriage Law enacted was recognized as ijtihad by maslahah murs- alah method. This method used to give a benefit for child with the deviations of Art. 7 (d) Islamic Law Compilation. But, this judgment still have not enough legal considerations, so that should be added other legal considerations such as the Child Protection Law, Regulations on Citizenship Ad- ministration, and also the stressing on understanding of Art. 2 (1) of Marriage Law. The condition of acceptance (itsbat) of marriage which occurred in Judgment No. 11/pdt/2016/Mkd submitted by the husband and wife, can be categorized as the application of voluntair, that the products is designation.